CCL27 Is Downregulated by Interferon Gamma via Epidermal Growth Factor Receptor in Normal Human Epidermal Keratinocytes. Issue 12 (December 2014) - Karakawa, Masaru; Komine, Mayumi; Hanakawa, Yasushi; Tsuda, Hidetoshi; Sayama, Koji; Tamaki, Kunihiko; Ohtsuki, Mamitaro
<x xml:space="preserve">Abstract</x> The cutaneous T cell‐attracting chemokine (CTACK)/CCL27 is indispensable in skin inflammation. CTACK/CCL27 is exclusively produced by epidermal keratinocytes to attract CCR10‐expressing T lymphocytes to the skin. We investigated the mechanism of CTACK/CCL27 production from normal human epidermal keratinocytes (NHEKs) by the proinflammatory cytokines TNFα and IFNγ. CTACK/CCL27 production was induced by TNFα via ERK, JNK, p38, and NFκB. The induction of CTACK/CCL27 by TNFα was suppressed by IFNγ via a pathway dependent on JAK, STAT1, and STAT3. Our results also demonstrated that IFNγ and TNFα induced the phosphorylation of EGFR and the following phosphorylation of ERK, which is partly responsible for the suppressive effect of IFNγ on TNFα‐induced production of CTACK/CCL27. Peri‐lesional skin of psoriasis demonstrates early inflammatory changes as we have previously reported. CTACK/CCL27 expression was diffuse in the peri‐lesional epidermis, while it was restricted to basal layer in lesional epidermis, suggesting that CTACK/CCL27 expression was induced in the early stage of psoriatic plaque formation, and IFNγ could participate in the suppression of CTACK/CCL27 expression in the lesional epidermis, reflecting the later stage of psoriatic plaque formation. Our study suggests that CTACK/CCL27 may have a pivotal role in the early stage of psoriasis plaque formation, but should be downregulated in the later stage to induce inflammation characteristic for chronic psoriasis plaques. J. Cell. Physiol. 229: 1935–1945, 2014. © 2014 Wiley Periodicals, Inc.